2007
DOI: 10.1002/ca.20507
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid sinus: An anatomic and endoscopic study in Asian cadavers

Abstract: An anatomic and endoscopic study of 48 cadaveric heads (96 sphenoid sinuses) was undertaken to describe the anatomy of the sphenoid sinus in Asians. Sellar type of sphenoid sinus is the most common, present in 53 out of 96 sides (55%). Forty-five of the 48 heads had a dominant sphenoid cavity, of which 11 contained vital structures from both sides of the sphenoid sinus. The incidence of accessory septae, carotid artery, optic nerve, maxillary nerve, and vidian nerve bulges were 70.8%, 67.7%, 69.8%, 61.5%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 19 publications
7
53
1
3
Order By: Relevance
“…In the studies performed, it was shown that the presence of Onodi cells was greater in Asian cadavers than in Western cadavers [10]. Therefore, during surgery, surgeons should be aware of the significantly greater presence of Onodi cells in Asian populations because the most common complication during transsphenoidal surgery is cerebrospinal fluid leak (CSF) leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies performed, it was shown that the presence of Onodi cells was greater in Asian cadavers than in Western cadavers [10]. Therefore, during surgery, surgeons should be aware of the significantly greater presence of Onodi cells in Asian populations because the most common complication during transsphenoidal surgery is cerebrospinal fluid leak (CSF) leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the protrusions is quite variable, which may affect the success of transsphenoidal endoscopic surgery [6,[8][9][10][11][12][13]. The prevalence of protrusion of ICA is not conclusive, ranging from 5.2% [14] -32.8% [15], 48.5% [16] and 67.7% [8], depending on the degree of individual pneumatization and the definition used in each study. From these results, the distances between these structures and the wall of SS and the prevalence of ptotrusions in SS were found proportion to the degree of SS pneumatization [7], but the quantitative evaluation SS volume was not indicated.…”
Section: The Relationship Between Ss Volume and Transsphenoidal Surgimentioning
confidence: 99%
“…There is a major risk of adverse events when there is poor orientation and a blind operation is performed. There is marked projection of the posterior ethmoid cells over and into the sphenoid sinus in 8.4-25% of the cases [1,12,14,17,19]. This often makes sphenoid sinus identification even more difficult and at times dangerous.…”
Section: Discussionmentioning
confidence: 99%